Cyclooxygenase (COX)-2 Inhibitors Reduce Toxoplasma gondii Infection and Upregulate the Pro-inflammatory Immune Response in Calomys callosus Rodents and Human Monocyte Cell Line - Pereira, Ana Carolina Alcântara; Silva, Rafaela José; Franco, Priscila Silva; de Oliveira Gomes, Angelica; Souza, Guilherme; Milian, Iliana Claudia Balga; Ribeiro, Mayara; Rosini, Alessandra Monteiro; Guirelli, Pâmela Mendonça; Ramos, Eliézer Lucas Pires; Mineo, Tiago Wilson Patriarca; Mineo, José Roberto; et al. (Frontiers in Microbiology, 2019)
Toxoplasma gondii is able to infect a wide range of vertebrates, including humans. Studies show that cyclooxygenase-2 (COX-2) is a modulator of immune response in multiple types of infection, such as Trypanosoma cruzi. However, the role of COX-2 during T. gondii infection is still unclear. The aim of this study was to investigate the role of COX-2 during infection by moderately or highly virulent strains of T. gondii in Calomys callosus rodents and human THP-1 cells. C. callosus were infected with 50 cysts of T. gondii (ME49), treated with COX-2 inhibitors (meloxicam or celecoxib) and evaluated to check body weight and morbidity. After 40 days, brain and serum were collected for detection of T. gondii by real-time PCR and immunohistochemistry or cytokines by CBA. Furthermore, peritoneal macrophages or THP-1 cells, infected with RH strain or uninfected, were treated with meloxicam or celecoxib to evaluate the parasite proliferation by colorimetric assay and cytokine production by ELISA. Finally, in order to verify the role of prostaglandin E2 in COX-2 mechanism, THP-1 cells were infected, treated with meloxicam or celecoxib plus PGE2, and analyzed to parasite proliferation and cytokine production. The data showed that body weight and morbidity of the animals changed after infection by T. gondii, under both treatments. Immunohistochemistry and real-time PCR showed a reduction of T. gondii in brains of animals treated with both COX-2 inhibitors. Additionally, it was observed that both COX-2 inhibitors controlled the T. gondii proliferation in peritoneal macrophages and THP-1 cells, and the treatment with PGE2 restored the parasite growth in THP-1 cells blocked to COX-2. In the serum of Calomys, upregulation of pro-inflammatory cytokines was detected, while the supernatants of peritoneal macrophages and THP-1 cells demonstrated significant production of TNF and nitrite, or TNF, nitrite and MIF, respectively, under both COX-2 inhibitors. Finally, PGE2 treatment in THP-1 cells triggered downmodulation of pro-inflammatory mediators and upregulation of IL-8 and IL-10. Thus, COX-2 is an immune mediator involved in the susceptibility to T. gondii regardless of strain or cell types, since inhibition of this enzyme induced control of infection by upregulating important pro-inflammatory mediators against Toxoplasma.